Ethnoscience E-Supplement for Critical Thinking and Cognitive Outcomes - Wardana, Irfan Ihza; Saptono, Sigit; Dewi, Novi Ratna (Unnes Science Education Journal, 2025)
Most education systems have not fully supported the development of students’ critical thinking skills, partly due to the limitations of teaching materials that only refer to textbooks. Complex material such as Earth Structure requires a more contextual and meaningful approach. One strategy that can be used is the development of ethnoscience-laden e-supplementary teaching materials that link the material with local wisdom. This study aims to analyze the validity, practicality, effectiveness, and characteristics of Ethnoscience-Laden E-Supplement Teaching Materials to improve students’ critical thinking skills and cognitive learning outcomes. The research used the ADDIE development model with instruments in the form of questionnaires, validation sheets, pretests, and posttests. The results showed that the E-Supplement was feasible to use in learning, with material validity of 94% and media of 95% (very valid category). The E-Supplement was also effective in improving critical thinking skills (average 69%, high category) and cognitive learning outcomes (N-Gain 61%, moderately effective category). Practicality was rated very well by teachers (97.67%) and students (85%). The characteristics of the E-Supplement are contextual, practical, and easy to use, and they raise the ethnoscience of the Sikidang Crater legend to increase student involvement and understanding in learning.